Sorption behavior of MgH2-Ti for Hydrogen storage material prepared by high pressure milling. Issue 1 (May 2021) - Malahayati; Nurmalita; Ismail; Machmud, M N; Jalil, Z
Abstract: Synthesis by reactive ball milling under hydrogen atmosphere is a potential technology for preparation of hydrogen storage materials. In this report we proposed a high pressures reactive milling (hereafter referred as "HPRM") for preparing the MgH2 -Ti. Nanocrystalline materials of MgH2 -Ti which is have been synthesized under high pressures hydrogen up to 9 MPa at room temperature. The characterization has been done by X-ray diffraction, scanning electron microscopy for their phase composition and morphology, respectively. Hydrogen storage capacities and the hydriding/dehydriding kinetics measured with gravimetric method. The X-ray diffraction pattern after 12 h of milling showed very broadened peaks, indicating that the crystal size was already in nanometers. It was also observed that the kinetics are fast which works within less than 7 mins for absorption (at 300°C, 10 bar H2 ) and within 6 mins for desorption (at 350°C, 50 mbar H2 ), respectively. The hydrogen storage capacity was 2.7 wt%.